Multimode nonlinear simulation technique having near-linear scaling with mode number in circular symmetric waveguides: publisher's note - Laegsgaard, Jesper (Optics letters, 2020)
This publisher's note contains a corrections to Opt. Lett.45, 4160 (2020).OPLEDP0146-959210.1364/OL.398412.This publisher's note contains a corrections to Opt. Lett.45, 4160 (2020).OPLEDP0146-959210.1364/OL.398412.